Mapping‐by‐sequencing in complex polyploid genomes using genic sequence capture: a case study to map yellow rust resistance in hexaploid wheat. (18th July 2016) - Gardiner, Laura‐Jayne; Bansept‐Basler, Pauline; Olohan, Lisa; Joynson, Ryan; Brenchley, Rachel; Hall, Neil; O'Sullivan, Donal M.; Hall, Anthony
Summary: Previously we extended the utility of mapping‐by‐sequencing by combining it with sequence capture and mapping sequence data to pseudo‐chromosomes that were organized using wheat– Brachypodium synteny. This, with a bespoke haplotyping algorithm, enabled us to map the flowering time locus in the diploid wheat Triticum monococcum L. identifying a set of deleted genes (Gardiner et al ., 2014). Here, we develop this combination of gene enrichment and sliding window mapping‐by‐synteny analysis to map the Yr6 locus for yellow stripe rust resistance in hexaploid wheat. A 110 MB NimbleGen capture probe set was used to enrich and sequence a doubled haploid mapping population of hexaploid wheat derived from an Avalon and Cadenza cross. The Yr6 locus was identified by mapping to the POPSEQ chromosomal pseudomolecules using a bespoke pipeline and algorithm (Chapman et al ., 2015). Furthermore the same locus was identified using newly developed pseudo‐chromosome sequences as a mapping reference that are based on the genic sequence used for sequence enrichment. The pseudo‐chromosomes allow us to demonstrate the application of mapping‐by‐sequencing to even poorly defined polyploidy genomes where chromosomes are incomplete and sub‐genome assemblies are collapsed. This analysis uniquely enabled us to: compare wheat genome annotations; identify the Yr6 locus – defining a smaller genic region than was previously possible; associate the interval with one wheat sub‐genome and increase the density of SNP markers associated. Finally, we built the pipeline in iPlant, making it a user‐friendly community resource for phenotype mapping. Significance Statement: It is challenging to apply mapping‐by‐sequencing pipelines to large polyploid genomes such as hexaploid wheat. Here we present a method for the rapid mapping of genes responsible for a phenotype, and demonstrate its utility by mapping a disease resistance gene. We show that our bespoke mapping‐by‐sequencing pipeline, available on iPlant, can be applied to poorly defined polyploid genomes.